The effect of learning interest and self-efficacy on junior high school students' learning achievement - Abdi, Sofyan; Rahmania, Dina (Universitas Negeri Yogyakarta, 2023)
This study aims to determine the effect of learning interest and self-efficacy on learning achievement. The population used is all students of class IX, with a sampling technique using random sampling of 72 students. The data collection technique used was a questionnaire and then analyzed with descriptive statistics. The results of this study indicate that there is an effect of interest in learning on learning achievement based on the partial test of 5.067> 2.291 with a significant 0.000 < 0.05, it can be said to be significant, there is also an effect of self-efficacy on learning achievement, with the test results showing a partial test of 3.659> 2.291 with a significant 0.000 < 0.05, it can be said that it is also significant, then interest in learning and efficacy also have a significant effect simultaneously (together) on student achievement of 51,489 > 3.127. The value of R Square is 0.599 or 59.9% and the remaining 0.41 or 40.1% is influenced by other variables outside the variables of interest in learning and self-efficacy. Such as learning motivation, learning facilities, teacher communication skills, family environment, and students' emotional intelligence.